Will different sagittal and vertical skeletal types relate the soft tissue thickness: A study in Chinese female adults. (February 2020) - Chu, Guang; Han, Meng-qi; Ji, Ling-ling; Li, Mu-jia; Zhou, Hong; Chen, Teng; Guo, Yu-cheng
Highlights: The greatest difference was observed in the upper lip region of maxilla and the mental region of mandible. The concave and hypodivergent skeletal type showed thickest soft tissue in maxillary region. The convex, and hyperdivergent skeletal type showed thickest soft tissue in mental region. Considering the variances of different skeletal types to obtain more accurate reconstruction results. Abstract: Facial reconstruction is a classical technique in forensic anthropology to reestablish the contours of the soft tissues over the skull. The accurate facial soft tissue data plays an essential role in forensic facial reconstruction. However, according to previous studies, various skeletal types might relate to different thickness in facial soft tissue. Until now, there are few publications focusing on the relationship between facial soft tissue thickness (FSTT) and different skeletal types, and none of them analyze the FSTT according to various sagittal and vertical skeletal types. The aim of this study was to testify the possible existence of correlations between FSTT and different skeletal types. In order to exclude interference from age, sex, ethnicity and body mass index (BMI) factors, we collected lateral projection X-rays data of 270 Chinese female aged 19–26 years with nomal BMI and divided them into various skeletal groups. Soft tissue thickness measurements were mainly based on 10 anthropological landmarks of the skull and statistics were analyzed on the basis of different skeletal types. The greatest differences were observed in the upper lip region of maxilla and the mental region of mandible. The concave and hypodivergent skull types showed the thickest soft tissue in maxillary region, and the convex and hypedivergent skull types showed the thickest soft tissue in the mental region. This study provided a database for FSTT according to various skeletal types in Chinese female population, and our current studies demonstrated that considering various skeletal types will improve the accuracy of facial reconstruction.